Garden calendar for March-April - Janakiram, T.; Jain, Ritu; Namita, Namita; P, Pavan Kumar (Indian Horticulture, 2019)
March is the month when actual spring starts with rising in temperature steadily. n first week of March, flower shows and exhibitions are conducted. Since temperature starts rising, so there is a need to maintain the moisture level, keep the garden weed-free and check for the infestation of insect pest and diseases. Seed of some of winter season flowers is ready to harvest.Tuberose, amaryllis and zephyrenthes can be planted. In April, enjoy beauty of flowering trees like Bauhinia alba, Butea monosperma, Erythrina blekii, Lagerstoremia speciosa, Peterospermum acerifolium, Callistemom lanceolatus, Tabebuia and spectabilis, Spathodea campanulata; shrubs like Buddelia, Barleria and climbers like bougainvillea, golden shower, and yellow jasmine (Jasminum humile). In gladiolus and roses, flowering is over, so remove dry and faded flowers.